(untitled) (Transport systems and technologies, 2021)
The problem of breaks automatic coupling is becoming urgent for outbound transport. in the robot, a number of defects are shown, which were found in the damaged car parts. Carrying out an analysis of the equipment of the vehicle will indicate the presence of a stock of performance, and if there is a defect in the deteriorated parts of the vehicle, it will be overwhelmed by the stock. An analysis of the normative documentation and methods in the control of car breakdowns is necessary to provide information on the methods of ruinous and non-rudimentary control, so that it can be done when preparing and repairing car breakdowns. Tom found the crocodile in the first place in the world of problems and is to blame for the increase in the quality of control to the body of the vehicle. Proponent is the acoustical control, and the very thin or mirror-thin method for the control of the shank of the autozchep in the screw hole before the wedge of the traction clamp. The robots of the methods runtuyu on the change in the amplitude of the signal when passing through the discontinuity of the metal, which allows the appearance of internal defects. These methods allow the appearance of significant internal defects such as metal discontinuities, but also to reduce the speed of car breakdowns through the appearance of this type of defect. On the basis of the obvious methods for the control of internal defects, the methods are projected that are irregular and can be stagnated to all auto-breakdowns due to minor preparation of the surface for control.